KARAKTERISTIK RUMAHTANGGA PETANI MISKIN DALAM MENGHADAPI PERMASALAHAN SOSIAL EKONOMI AKIBAT KENAIKAN HARGA DAN KELANGKAAN BAHAN BAKAR MINYAK (BBM) DI PEDESAAN - Dumasari Dumasari; Tri Na’imah (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2008)
Some problems of poorness specially faced by peasant society circle in the reality remain to be something matter of urgen to be paid attention by various related parties. Internal and external factors manner partake to depress difficulty of quit of poor peasant household shackle squeezing. As for one of the factor which lately follow added economic burden of poor peasant household more and more weight is increase reality and rare of oil fuel (BBM). Along with the mentioned hence this research aim to identify characteristic of poor peasant household which is being face problems of economic social effect of increase of price reality and rare of BBM in rural. Research location specified intentionally in Village of Gandatapa and Village of Sikapat, Banyumas. Method research the used is descriptive case study with approach qualitative. Research informan determined designedly pursuant to various elementary consideration. Research result indicate that characteristic of poor peasant household which is being face problems of economic social of increase of price effect and rare of BBM in rural vary to be evaluated from: income, farm status of land, especial maintenace pattern type, status ownership of house remain, economic burden, wide of farm of land and also opportunity do conduct peripheral maintenace pattern. Characteristic of informant household to develop strength for coping strategies mechanism for overcoming problems economic social of increase of price reality effect and rare of BBM at rural. Key words : characteristic of poor peasant household, problems of economic social, increase of price and rare of oil fuel